2018
DOI: 10.1002/jbm.b.34179
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetrical dual coating on the stent prepared by ultrasonic atomization

Abstract: This study aims to design an asymmetric dual coating (ADC) on the stent by ultrasonic atomization to solve the problem of delayed endothelialization and late or very late stent thrombosis which caused by drug eluting stent (DES) with symmetric coating. Chitosan loaded monoclonal platelet glycoprotein IIIa receptor antibody SZ-21 coating (CSC) was sprayed on inner surface of stents, and outer surface was sprayed CSC and poly(lactic-co-glycolic acid) (PLGA) loaded with docetaxel (DTX) coating (PDC). The coated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The aqueous soluble GO-copper nanocomposites coating enhances the adhesion and osteogenic differentiation of rat bone marrow stem cells [36], heparin-loaded GO coating on titanium surface improved the blood compatibility and endothelial cell behaviors [37]. In this research, we prepared the coating using ultrasonic atomization spraying which has been proved to get high quality coatings from our previous studies [15, 16, 38] and the designed double-layer coating greatly increased the biocompatibility of GO and implemented the multifunction of the coating with loaded multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aqueous soluble GO-copper nanocomposites coating enhances the adhesion and osteogenic differentiation of rat bone marrow stem cells [36], heparin-loaded GO coating on titanium surface improved the blood compatibility and endothelial cell behaviors [37]. In this research, we prepared the coating using ultrasonic atomization spraying which has been proved to get high quality coatings from our previous studies [15, 16, 38] and the designed double-layer coating greatly increased the biocompatibility of GO and implemented the multifunction of the coating with loaded multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The stent-spraying system and coating steps was shown in Fig. 1 [15, 16]. The bare metal stents were immersed in the 2 mg/ml DA solution (pH 8.5 Tris Buffer) for 12 h. DTX was dissolved in GO solution (2 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Docetaxel-coated stents showed antiproliferative effect on vascular SMCs and inhibited intimal hyperplasia and neointima formation in animal studies. 43,44 Docetaxel administered directly to injured vessel sites using a local drug delivery catheter was effective in inhibiting the proliferation of intimal SMCs and neointimal hyperplasia in animal studies. 45,46 Although many issues associated with arterial angioplasty procedures may limit the clinical application of these methods, these studies have shown that docetaxel can prevent atherogenic SMC proliferation in the arterial intima.…”
Section: Hdl Biogenic and Antiatherogenic Effects Of Docetaxelmentioning
confidence: 99%